2019
DOI: 10.2807/1560-7917.es.2019.24.19.1900256
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of ceftazidime-avibactam-resistant Klebsiella pneumoniae during treatment, Finland, December 2018

Abstract: In December 2018, a ceftazidime-avibactam (CAZ-AVI)-resistant KPC-2-producing Klebsiella pneumoniae strain was isolated in Finland. CAZ-AVI resistance was observed 34 days after CAZ-AVI treatment in a trauma patient transferred from a hospital in Greece who had been colonised with bla KPC-2 -producing K. pneumoniae ST39, and later developed a bloodstream infection. The CAZ-AVI-resistant strain contained a novel 15 amino acid insertion in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 8 publications
3
29
0
Order By: Relevance
“…Shields et al (2017) has reported on the acquisition of CAZ-AVI resistance among ST258 KPC-KP during treatment in the United States. After that, (Raisanen et al, 2019) isolated a ST39 KPC-KP that was resistant to CAZ-AVI after this combination treatment. In China, ST11 KPC-KP is commonly prevalent (Chen et al, 2014;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Shields et al (2017) has reported on the acquisition of CAZ-AVI resistance among ST258 KPC-KP during treatment in the United States. After that, (Raisanen et al, 2019) isolated a ST39 KPC-KP that was resistant to CAZ-AVI after this combination treatment. In China, ST11 KPC-KP is commonly prevalent (Chen et al, 2014;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In China, ceftolozane-tazobactam has not yet been approved, and ceftazidime-avibactam was only approved on 8 September 2019. Unfortunately though, ceftazidime-avibactam-resistant CRKP has already been reported in various countries [ 22 , 23 ]. Therefore, to prevent the development of novel ceftazidime-avibactam-resistant strains in China, identification of the resistance mechanisms should be a prerequisite to developing rational antibiotic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…This ␤-lactam/␤lactamase inhibitor combination provides a therapeutic alternative for treating infections caused by KPC-like and OXA-48-like producers, whereas producers of carbapenemases of the metallo-␤-lactamase type remain resistant to that combination (1,2). Despite CZA being rarely prescribed worldwide, KPC-like-producing isolates resistant to this drug combination have already been reported (3)(4)(5)(6)(7). Several reports identified KPC variants exhibiting single-amino-acid substitutions in their omega-loop (amino acid positions 164 to 179), particularly the Asp179Tyr substitution, leading to enhanced affinity toward ceftazidime with a concomitant reduced binding to avibactam (AVI) (8)(9)(10)(11)(12).…”
mentioning
confidence: 99%